Digital Readiness and Social Capital in Shaping Entrepreneurial Intentions: The Mediating Role of Risk Tolerance among University Students - Valerie Thalia. S; Astri Ayu Purwati; Ermina Rusilawati; Zulfadli Hamzah (International Journal of Information System and Innovation Management (IJISIM), 2025)
Entrepreneurial intention needs to be cultivated and strengthened among students as a strategic effort to address the issue of unemployment in Indonesia. This study aims to examine the roles of social support, digital literacy, and risk tolerance in shaping students’ entrepreneurial intentions. The research was conducted among students of the Pelita Indonesia Institute of Business and Technology, Pekanbaru, Riau. The population consisted of 2,203 undergraduate students enrolled in 2023, from which 100 students were selected as respondents. A simple random sampling technique was employed to ensure that each member of the population had an equal opportunity to be selected, without considering specific strata or characteristics (Sugiyono, 2019). Data were analyzed using multiple linear regression. The findings indicate that social support and risk tolerance have a positive and significant effect on entrepreneurial intentions, whereas digital literacy shows a negative and insignificant effect.